Antibacterial activity of novel Cu2ZnSnS4 nanoparticles against pathogenic strains. Issue 129 (15th December 2015) - Kumar, R. Saravana; Maddirevula, Sateesh; Easwaran, Maheswaran; Dananjaya, S. H. S.; Kim, Moon-Deock
Abstract : Cu2 ZnSnS4 nanoparticles exhibited robust antibacterial activity against the pathogenic Gram-positive and Gram-negative bacteria. Abstract : In the present work, tube-shaped Cu2 ZnSnS4 (CZTS) particles were synthesized by a facile reflux method. Structural, morphological and optical analysis by X-ray diffraction, Raman spectroscopy, scanning electron microscopy and UV-vis diffused reflectance spectroscopy confirmed the formation of tetragonal CZTS with a band gap of 1.44 eV exhibiting hollow tube-shaped morphology. The antibacterial activity of the synthesized CZTS particles towards the pathogenic Gram-positive ( Staphylococcus haemolyticus, Staphylococcus aureus aureus ) and Gram-negative ( Aeromonas hydrophila, Aeromonas salmonocida masoucida, Escherichia coli ) bacteria was investigated by determining the minimum inhibitory concentration and zone of inhibition. Experimental results showed that the synthesized CZTS particles possess robust antibacterial activity, as good as Ag nanoparticles and ampicillin against the tested bacteria.